Geological and geotechnical characterization of Ziragn Dam sitting, northwestern Ethiopia - Degu Birhanu; Chalachew Tesfa (Environmental and Sustainability Indicators, 2023)
The goal of this study was to look at the geological and geotechnical conditions of the Ziragn dam, which would be built across the Ziragn river for irrigation purposes. The objectives of the study were to investigate and characterize the geological, hydrogeological, and seismicity condition, reservoir area, construction materials, and geotechnical situations of the dam site. During the physical investigation, geotechnical interpretations were done using the drilling logged data, laboratory tests as well as drilling core samples. Results of the study revealed that the area is characterized by slightly fractured massive basaltic rocks which are found at the dam axis and spillway area. The reservoir area is also covered by silty clay soils basaltic rocks and silty clay soil. The stream bed and the banks are made up of the same geological materials of basaltic rock. The basaltic rocks at the reservoir area are characterized by low permeability while the abutment areas were moderately fractured and weathered and the silty clay soil is characterized by medium to high plastic impervious soil. Based on the findings, the following recommendations are forwarded: (a) Design a masonry/concrete cut-off wall at the central portion of the dam. (b) On the left bank at the upstream, vertically jointed rocks permitted seepage problems, it needs cement grouting. (c)Rocks at the abutment sides show fractured and weathered which needs the removal of the surface and treatment by cement injection. (d) Even though the dam was micro it needs serious monitoring and follow-up during and after construction.